Edukasi Pengelolaan Sampah dan Pemberdayaan Masyarakat melalui CEMOT (Cerdas Mengelola Sampah Dengan Maggot) - Muhammad Fadli Ramadhansyah; Muhammad Iqbal; Riefqa Naufalia Hanifah; Alivia Izfana; Salwa Fitria; Agnis Ika Pratiwi; Nadila Awalia Fitri; Fayyaza Aqila; Inara Perdana Kurnia; Alif Indah Melani; Haura Duanna; Dyah Utari; Dinda Sinta Rahayu (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2026)
The problem of organic waste accumulation in RW 011, Cipayung Village, is increasingly crucial due to the limited capacity of the landfill and the discourse of suspending waste collection. This condition risks causing environmental pollution and health problems. The CEMOT community service activity was carried out to increase public knowledge and awareness regarding waste sorting and organic waste management using Black Soldier Fly larvae (maggots) as bioconversion agents. Activities using educational-participatory design through counseling, maggot cultivation demonstrations, and mentoring were conducted. Evaluation was carried out using pre-test and post-test questionnaires on 17 participants, accompanied by observations of the practical process. The Wilcoxon test results showed a significant difference between the pre-test and post-test scores (p = 0.009), with an increase in the mean score from 5.2 to 8.0, indicating an increase in participants' knowledge regarding maggot-based organic waste management. Qualitatively, participants showed enthusiasm and interest in implementing maggot cultivation at home, although there were still limitations in participation and program sustainability. CEMOT has the potential to become a model for adaptive and sustainable community-based organic waste management.